Whispers of Wisdom: A Qualitative Case Study on Character Education through Dodaidi Lullabies in Aceh’s Early Childhood - Munawwarah, Munawwarah; Astuti, Sri; Futhira, Nadia; Rahmi, Isramatur (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study explores the values of local wisdom embedded in Dodaidi lullabies as perceived by caregivers in Acehnese communities, with the aim of identifying and analyzing character values expressed through this traditional oral form. Rather than evaluating outcomes in children, the study focuses on how parents and community figures view Dodaidi as a cultural medium for transmitting values in early childhood. Dodaidi represents a unique combination of musical art, oral tradition, and cultural symbolism that reflects the moral and spiritual aspirations of Acehnese society.Design/methods/approach – A qualitative case study approach was employed, with data collected through interviews, observations, and document analysis to investigate how Dodaidi is practiced and interpreted within informal family education settings.Findings – The study identified key values that are embedded in Dodaidi lyrics according to parental and community perspectives: (1) unity and faith; (2) worship and religious practice; (3) reverence for parents and teachers (takzim); (4) social empathy and manners; and (5) responsibility and a strong work ethic.Research implications/limitations – This study presents Dodaidi as a cultural expression perceived by caregivers to support informal character education. However, it does not assess its actual impact on children’s development. The study relies on adult perspectives and does not examine how abstract values like faith or responsibility are internalized by young children, especially those who may not yet comprehend the lyrics. Thus, conclusions are limited to perceived functions rather than proven effectiveness.Practical implications – Dodaidi is typically sung by parents or grandparents during bedtime, blending affectionate interaction with the transmission of values and cultural identity. Its preservation can support cultural continuity in early childhood education.Originality/value – The research contributes to discourse on culturally rooted educational practices by documenting how traditional lullabies such as Dodaidi are understood as moral resources within family life. It encourages greater appreciation for oral traditions as part of local strategies for value-based education.Paper type Case study